Distracted driving: mobile phone use while driving in three Mexican cities. Issue 4 (24th November 2012) - Vera-López, Juan Daniel; Pérez-Núñez, Ricardo; Híjar, Martha; Hidalgo-Solórzano, Elisa; Lunnen, Jeffrey C; Chandran, Aruna; Hyder, Adnan A
Abstract : Mexico has a significant road traffic injury and mortality burden, and several states/municipalities have begun passing legislation restricting mobile phone use while driving (MPUWD). Little information is available about the prevalence of MPUWD in Mexico. This study measures the prevalence of mobile phone talking and texting among drivers in three cities, and identifies associated demographic and environmental factors. Two rounds of roadside observations from a group of randomly selected automobile drivers were conducted during 2011–2012 in Guadalajara-Zapopan, León and Cuernavaca. The overall prevalence of MPUWD was 10.78%; it was highest in Guadalajara-Zapopan (13.93%, 95% CI 12.87 to 15.05), lowest in Cuernavaca (7.42%, 95% CI 6.29 to 8.67), and remained stable over two rounds of observations, except for León, where the prevalence increased from 5.27% to 10.37% (p=0.000). Driving alone on major roads in non-taxi cars during the weekdays was associated with MPUWD. Results highlight the importance of studying the risk of mobile phone use, and designing and evaluating specific preventive interventions to address this problem in Mexico.